The European Audiovisual Communication Directive and the Actual Regulation of the Obligation of Early Financing of European Works for the Video on Demand Segment (Law, State and Telecommunications Review, 2019)
Purpose ”“ Demonstrate how the European Union regulates the obligation of early financing of European works for the segment of video on demand as well as the regulation in each of the 28 Member States of the European Union.Methodology/approach/design ”“ Present the historical evolution for the comprehension of what were the reasons for this non-harmonization and analyse the legislation of each member of the European Union to demonstrate that contradiction.Findings ”“ A Directive is a legal instrument of the European Union to standardize legislation. However, regarding the imposition of the obligation of early financing of European works for the segment of video on demand, there is no standardization of national legislations.Value ”“ Establish the European model for the regulation of the advance financing of European works for the video on demand segment to know if it can be a model for States which hasn’t regulated yet this segment (such as Brazil).